SACROILIITIS IN PATIENTS WITH ANKYLOSING SPONDYLITIS: THE FINDINGS OF MAGNETIC RESONANCE IMAGING - L. Oktay Erdem,; C. Zuhal Erdem,; Selda Sarıkaya, (Archives of Rheumatology, 2004)
Objective: To determine the characteristic findings of sacroiliitis using by magnetic resonance (MR) imaging. Material and Method: 13 consecutive patients with AS (mean age: 44± 10years) and 4 volunteers (mean age:40± 7 years) were enrolled in the study. Mean disease duration of AS patients was 10.4± 8.3 years (4- 30 years). MR images were performed with the sequences of the coronal T1 weighted turbo spin-echo (TSE) image, T2 weighted FFE image and STIR image using a 1.5-T imager for all volunteers and patients. 26 sacroiliac (SI) joints in 13 patients with AS were examined with MR examination. Erosions, ankylosis, and type 1-3 findings in the SI joints were recorded on MR imaging. MR image set was interpreted by consensus of two radiologist who blinded clinical data. Results: MR imaging findings were normal in 4 volunteers (8 SI joints ). The most common abnormalities detected by MR imaging in 13 AS patients were as follows, type 3 lesions (46%), type 2 lesions (31%), type 1 lesions (19%), erosions (38%) and ankylosis (35%). Conclusion: We belived that MR imaging is an useful diagnostic modality in the diagnosis of sacroiliitis which can demonstrate detailed anatomy of the SI joint and the changes of sacroiliitis and the lack of radiation exposure.